A revised embedded planning tool for intensive reading instruction - Wei, Yan; Lombardi, Allison; Simonsen, Brandi; Coyne, Michael; Faggella-Luby, Michael; Freeman, Jennifer; Kearns, Devin (Learning Disabilities: A Multidisciplinary Journal, 2017)
Keywords: dept.rdg; dept.sed

Leveraging information technology literacy to enhance college and career readiness for secondary students with disabilities - Lombardi, Allison; Izzo, Margo V.; Gelbar, Nicholas; Murray, Alexa; Buck, Andrew; Johnson, Victor; Hsiao, Jay; Wei, Yan; Kowitt, Jennifer (Journal of Vocational Rehabilitation, 2017)
BACKGROUND: In the 21st century, information technology (IT) literacy is crucial for all students, and may better prepare students with disabilities for transition to postsecondary employment or education. OBJECTIVE: In this study, the potential of IT literacy embedded into an online transition curriculum is explored in the context of secondary special education. The curriculum aligns with Common Core State Standards in English Language Arts that are relevant to reading comprehension, writing, as well as searching for and analyzing sources of information online. METHODS: A quasi-experimental pretest-posttest design was utilized in six high schools. RESULTS: Findings show that intervention group students improved in IT literacy; whereas, comparison group students did not make similar gains. CONCLUSION: Implications for embedding transition services into specific courses and curricula for secondary students with Individualized Education Programs (IEPs) are discussed. © 2017-IOS Press and the authors. All rights reserved.
Keywords: Article; Transition; adolescent; attention deficit disorder; autism; career; career readiness; college; comprehension; controlled study; curriculum; dept.rdg; dept.sed; disability; education program; emotional disorder; employment; female; high school student; human; information technology; intellectual impairment; language disability; learning disorder; literacy; major clinical study; male; quasi experimental study; special education; technology; vocational education; writing